2016
DOI: 10.1371/journal.pone.0164424
|View full text |Cite
|
Sign up to set email alerts
|

8-Oxoguanine Affects DNA Backbone Conformation in the EcoRI Recognition Site and Inhibits Its Cleavage by the Enzyme

Abstract: 8-oxoguanine is one of the most abundant and impactful oxidative DNA lesions. However, the reasons underlying its effects, especially those not directly explained by the altered base pairing ability, are poorly understood. We report the effect of the lesion on the action of EcoRI, a widely used restriction endonuclease. Introduction of 8-oxoguanine inside, or adjacent to, the GAATTC recognition site embedded within the Drew—Dickerson dodecamer sequence notably reduced the EcoRI activity. Solution NMR revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…Provocatively, quantum mechanical calculations indicate that the addition of the carbonyl oxygen at C8 and a proton at N7 to guanine (forming 8-oxoG) causes a rotation of the base dipole by 42° ( 39 ), which would be expected to alter the electrostatic contribution to 8oxoG base stacking on its nearest neighbors despite the similarity in buried surface area, but in a way that is difficult to calculate precisely ( 40 ). Though sugar pucker at the 8oxoG-C pair appears to fall into the normal C2′ endo range ( 4 ), phosphorus NMR data hint that the backbone may switch from the normal BI to BII conformation adjacent to the lesion, with a corresponding reduction in twist ( 41 ). Though DNA melting experiments show only a small change in the measured melting temperature of 8oxoG-containing duplexes relative to the corresponding G-containing duplexes, the derived free energy change for melting is more significant, in agreement with the findings of this work ( 10 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Provocatively, quantum mechanical calculations indicate that the addition of the carbonyl oxygen at C8 and a proton at N7 to guanine (forming 8-oxoG) causes a rotation of the base dipole by 42° ( 39 ), which would be expected to alter the electrostatic contribution to 8oxoG base stacking on its nearest neighbors despite the similarity in buried surface area, but in a way that is difficult to calculate precisely ( 40 ). Though sugar pucker at the 8oxoG-C pair appears to fall into the normal C2′ endo range ( 4 ), phosphorus NMR data hint that the backbone may switch from the normal BI to BII conformation adjacent to the lesion, with a corresponding reduction in twist ( 41 ). Though DNA melting experiments show only a small change in the measured melting temperature of 8oxoG-containing duplexes relative to the corresponding G-containing duplexes, the derived free energy change for melting is more significant, in agreement with the findings of this work ( 10 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though DNA melting experiments show only a small change in the measured melting temperature of 8oxoG-containing duplexes relative to the corresponding G-containing duplexes, the derived free energy change for melting is more significant, in agreement with the findings of this work ( 10 , 38 ). A combination of calorimetric methods showed that this effect is associated with a slight reduction of the number of counterions and significant reduction of ∼15 water molecules upon substitution of 8oxoG-C for G-C ( 41 ). The 8oxoG-C duplex appears much less hydrated than the G-C duplex, due to additional O and H of the O8 and N7 atoms in the major groove.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported previously, TBI can induce persistent oxidative stress in HSCs which may cause sustained DNA damage and oxidative DNA damage [ 22 ]. 8-oxoguanine (8-oxoG) is a naturally abundant base and impactful oxidative DNA lesions with a well-characterized mutagenic potential [ 23 ]; it is easily generated in DNA by reactive oxygen species induced by TBI [ 24 ]. Our results showed that MFI of γ -H2AX and percentage of 8-oxoG positive cells increased significantly in irradiated c-kit + cells compared to control group, and HW consumption downregulated expression of γ -H2AX and 8-oxoG ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the pro-mutagenic (syn)oxoG:(anti)A mispair mimics the geometry of a correct base pair, it does not cause significant Interestingly, while X-ray and NMR structures show that DNA with oxoG lesion appears virtually identical to the corresponding unmodified duplex and the oxoG:C has a normal high-affinity Watson-Crick base pairing arrangement, thermodynamic studies indicate that oxoG has a local destabilizing effect on DNA (destabilizes oxoG:C and 5' flanking base pairs) [74,75]. The origin of this destabilization was attributed to the loss of a cation-binding site in the major groove (due to the replacement of an electronegative N7 with an electropositive N-H), reduction in the level of hydration and reduced base stacking [74] and to steric repulsion effects that propagate from O 8 via the sugar pucker to the 3 -phosphate [75,76]. It is possible that differences in local DNA stability and its conformational dynamics could affect DNA synthesis efficiency across oxoG.…”
Section: The Structural Basis Of Ambiguous Coding Potential Of Oxogmentioning
confidence: 99%